White matter hyperintensities and their role in major depressive episodes: a cross-sectional study in adults under 65 - Edouard Baudouin; Emmanuelle Corruble; Pietro Gori; Isabelle Bloch; Laurent Becquemont; Emmanuelle Duron; Romain Colle (Brazilian Journal of Psychiatry)
Objective: White matter hyperintensities (WMH) are associated with major depressive episodes (MDE) in individuals aged 65 and older. WMH are prevalent in adults under 65, yet the association between their volume and MDE in this population remains uncertain. This study aimed to assess the association of WMH volume with MDE and its severity in patients aged < 65. Methods: Cross-sectional study (ancillary to clinical trial NCT02051413) of subjects under the age of 65. Overall, 69 patients with MDE and 32 healthy controls (HCs) were included. Severity was assessed with the Hamilton Rating Scale (HRS) and WMH were quantified by two experts. Post-hoc mediation analyses were conducted if associations were found between independent variables and WMH. Results: Mean age was 34.5 (12.4) years. There was no difference in WMH between patients and HCs. Higher WMH volumes were observed in extremely severe MDE (2,170.2 [3,767.9] mm3 vs. 416.6 [594.9] mm3 [r = 0.21; p < 0.05]), which completely mediated the effect of age on severity. Conclusions: In a sample of adults under 65, this study failed to identify higher WMH volume in patients with MDE compared to HCs. However, WMH may act as a mediator of the association between age and MDE severity. This finding suggests that WMH could contribute to more severe depression in late life.